Psychometric properties of the short Warwick Edinburgh mental well-being scale (SWEMWBS) in service users with schizophrenia, depression and anxiety spectrum disorders - Janhavi Ajit Vaingankar (Health and Quality of Life Outcomes, 2017)
Abstract Background To establish the validity and reliability of the Short Warwick Edinburgh Mental Well-being Scale (SWEMWBS) in service users with schizophrenia, depression and anxiety spectrum disorders in Singapore and estimate SWEMWBS scores across socio-demographic and the three psychiatric diagnostic groups in the sample. Methods This secondary analysis was conducted using data from a study among outpatients of a tertiary psychiatric hospital. In addition to the SWEMWBS, socio-demographic data and current psychiatric diagnosis were collected. Service users were also administered the Global Assessment of Functioning (GAF), Patient Health Questionnaire (PHQ)-8, Generalised Anxiety Disorder (GAD)-7, Satisfaction with Life Scale (SWLS) and the Positive Mental Health (PMH) instrument. The SWEMWBS was tested for factorial validity, reliability and convergent and divergent validity. Results In total, 350 service users with a mean (SD) age of 39.1 (11.1) years were included in this study of which 39.4%, 38.9% and 21.7% had schizophrenia, depression and anxiety spectrum disorders, respectively. The single factor structure of the SWEMWBS was confirmed by confirmatory factor analysis (CFI = 0.969, TLI = 0.954, RMSEA = 0.029). The internal consistency reliability was high (Cronbach’s alpha = 0.89). The convergent and divergent validity testing revealed that the SWEMWBS scores had significant moderate to high positive correlations with GAF, SWLS and PMH scores and moderate negative correlations with (PHQ)-8 and (GAD)-7 scores. SWEMWBS scores were higher in married participants (22.2 (5.4) versus never married: 20.7 (5.3) and divorced/separated/widowed: 20.4 (5.1), p = 0.049) and among those with schizophrenia (22.8 (5.5) versus depression:19.6 (4.7) and anxiety spectrum disorders 20.9 (5.2), p < 0.001). Conclusion These results demonstrate adequate validity and reliability of the SWEMWBS in people with schizophrenia, depression and anxiety spectrum disorders in Singapore.